2001
DOI: 10.1007/pl00004198
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous beliefs, price dispersion, and welfare-improving price controls

Abstract: We consider a search market model where agents have heterogeneous beliefs about the distribution of prices. A suggestive example shows that Jevon's Law of One Price and standard welfare results are not robust to small heterogeneous errors in beliefs. In particular we show that a price ceiling above marginal cost can reduce price dispersion and improve welfare (by lowering aggregate search costs) without decreasing quantity supplied. These results are broadly consistent with the empirical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Behavioural models have been developed to bridge the gap between theory and empirical reality. Rauh (2001) shows that price dispersion can arise when sellers make small but heterogeneous mistakes in beliefs about the market price distribution. Baye and Morgan (2004) show that bounded rationality choice models, namely, quantal response equilibrium (QRE) (McKelvey and Palfrey, 1995) and ε-equilibrium (Radner, 1980) can explain price dispersion in homogeneousgood pricing games.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural models have been developed to bridge the gap between theory and empirical reality. Rauh (2001) shows that price dispersion can arise when sellers make small but heterogeneous mistakes in beliefs about the market price distribution. Baye and Morgan (2004) show that bounded rationality choice models, namely, quantal response equilibrium (QRE) (McKelvey and Palfrey, 1995) and ε-equilibrium (Radner, 1980) can explain price dispersion in homogeneousgood pricing games.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models of price dispersion are largely developed on the information cost regime (Burdett and Judd 1983;Reinganum 1979;Stiglitz 1977, 1985;Diamond 1987Diamond , 1993Rauh 2001). A detailed literature review on price dispersion can be found in Baye et al (2006).…”
Section: Previous Studiesmentioning
confidence: 99%
“…2 The reason is that if a capacity-constrained seller meets more than 1. Examples include the information heterogeneity in Baye, Kovenock, and De Vries (1992) and Varian (1980); the belief-heterogeneity in Rauh (2001); costly search as in Carlson and McAfee (1983) and Daughety (1992); the firm heterogeneity in Reinganum (1979); random search that limits price information as in Burdett and Judd (1983) and Butters (1977), or as in Burdett and Mortensen (1998) and Camera and Corbae (1999); and the predetermined shopping order in Arbatskaya (2007). 2.…”
Section: Introductionmentioning
confidence: 99%